Realization Limits of Impulse-Radio UWB Indoor Localization Systems - Zwirello, Lukasz (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2013)
In this work, the realization limits of an impulse-based Ultra-Wideband (UWB) localization system for indoor applications have been thoroughly investigated and verified by measurements. The analysis spans from the position calculation algorithms, through hardware realization and modeling, up to the localization experiments conducted in realistic scenarios. The main focus was put on identification and characterization of limiting factors as well as developing methods to overcome them.